Maternal transmission of multiple sclerosis in a dutch population. - Hoppenbrouwers, I; Liu, F; Aulchenko, Y; Ebers, G; Oostra, B; van Duijn, C; Hintzen, R (2008)
OBJECTIVE: To investigate the parental relationship of patients with multiple sclerosis (MS) from an extended pedigree with extensive genealogical information up to the middle of the 18th century. DESIGN: Multiple sclerosis is a complex disease resulting from genetic and environmental factors. Parent-of-origin effect, a phenomenon when the same allele may express differently depending on the sex of the transmitting parent, may influence the risk for MS. We investigated parental relationships between patients with MS using extensive genealogical information available from the Genetic Research in Isolated Populations program. We compared the average kinship of the parents of MS patients. We further explored the distribution of shortest genealogical links between parents of MS patients. Subjects Twenty-four MS patients from the isolated population who could be linked within a large complex pedigree, including 2471 people in total. RESULTS: The results consistently indicate a higher prevalence of maternal transmission of MS. The kinship between mothers of patients was 3.8 times higher than that between fathers (bootstrap P = .01). Among the 814 shortest connections between parents, 333 were maternal (40.9%, vs 25.0% expected), 98 were paternal (12.0%, vs 25.0% expected), and 383 were maternal-paternal (47.1%, vs 50.0% expected) (P < .001). CONCLUSIONS: Mothers of MS patients were more closely related than their fathers. This skewed relationship shows evidence for a maternal effect in MS. The most likely explanation is a gene-environment effect that takes place in utero.